Vessel Monitoring System (VMS) Technology as a Management Strategy for Longline Tuna Capture Fisheries in Benoa - Putu Ristia Amandari; I Ketut Wija Negara; Made Ayu Pratiwi; Nu'man Najib; Sapto Susilo (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Benoa Port has fishing vessel activities that are the foundation of Bali's tuna swamp fisheries (longlines). Sustainable tuna capture fisheries will be impossible to attain if the number of infractions in the marine and fisheries sectors continues to rise. The government's efforts to reduce infractions in marine and fisheries are achieved through tightening the oversight system. The Vessel Monitoring System (VMS) surveillance system was created to reduce breaches in the marine and fishery sectors. The goal of this study is to determine the monitoring and suspected indication of violations of longlines using the VMS at the Benoa PSDKP as well as to learn about the capture fisheries management strategy using VMS data on longlines at Benoa Port using an analytic hierarchy process (AHP) approach. This study used a qualitative-quantitative descriptive technique with AHP analysis to determine the value of the management priority scale. Based on the findings of monitoring longlines with web tracks from January to December 2022, the most targeted fishing area was the Indian Ocean High Seas, and the most prominent suspected indication of violation was the inactivity of VMS when the vessel was operating. The main approach for managing capture fisheries utilizing VMS data on longlines in Benoa Port with the AHP analysis is for the government to offer subsidies for installing VMS on all fishing vessels, particularly those under 30 GT.